Examining the effects of drinking and interpersonal protective behaviors on unwanted sexual experiences in college women. (March 2016) - Sell, Nichole M.; Turrisi, Rob; Scaglione, Nichole M.; Hultgren, Brittney A.; Mallett, Kimberly A.
Abstract: Introduction: Recent evidence suggests interpersonal protective behaviors (IPBs) may be more effective than alcohol-based strategies at decreasing alcohol-related sexual consequences. However, no studies have examined individual IPBs to assess their unique influences on specific sexual consequences. The current study used a longitudinal design to examine the direct effects of typical weekly drinking and specific IPBs on unwanted sex. IPBs were also examined as moderators of the relationship between drinking and unwanted sex. Methods: Randomly sampled female drinkers attending a northeastern university (N = 191) completed a baseline survey measuring typical weekly drinking and IPBs and a six-month follow-up assessing unwanted sex. Bootstrapped regression examined the effects. Results: Drinking predicted unwanted sex after accounting for IPBs (range of b s = .008–.009, SE = .005, 95% CI [.000, .02]). Vigilance-related IPBs were negatively associated with unwanted sex after controlling for drinking ( b  = −.052, SE = .025, 95% CI [−.107, −.008]). The IPB " Talking to people who know one ' s potential dating or sexual partner to find out what s / he is like " significantly moderated the drinking–unwanted sex relationship ( b  = −.009, SE = .004, 95% CI [−.018, −.003]). At above-average drinking levels, women who used this IPB more frequently reported fewer episodes of unwanted sex. Conclusion: Findings revealed obtaining information about a potential partner significantly reduced the impact of drinking on unwanted sex for heavier drinkers. Future research examining how women implement this IPB may clarify its role in reducing unwanted sex. Highlights: We examined the main effects of drinking and specific IPBs on unwanted sex. We examined whether specific IPBs moderated drinking's impact on unwanted sex. Drinking and unwanted sex were positively related when considering two IPBs. Vigilance IPBs and unwanted sex were negatively related after controlling drinking. The IPB "talking to people who know a potential partner" reduced drinking's impact.